Methodological framework for revitalisation of small-scale irrigation schemes in Southern Africa - Mwendera, Emmanuel; Chilonda, Pius (2013)
This paper presents a methodological framework for revitalising small-scale irrigation schemes which are no longer performing well due to a combination of infrastructural, social-economic, institutional and governance problems, among others. The framework was developed as part of a project to revitalise small-scale irrigation schemes in Masvingo Province in Zimbabwe. The framework is based on the understanding that an irrigation scheme consists of four mutually interlinked systems: the physical system, the cropping system, the economic system and the social-organisational system. The methodological framework combines both hardware and software rehabilitation processes to lead to a comprehensive revitalisation of an irrigation scheme. The framework consists of systematic steps which lead to achieving predetermined outputs, which then lead to intermediate outcomes and goal outcomes. The framework has indicative timelines for the steps. The application of the proposed framework and the hypothesis that improved understanding of existing scheme and improved training of farmers which result in sustainable and improved performance of revitalised irrigation schemes are yet to be investigated. However, the authors invite reaction of readers on the proposed methodological framework.